2021
DOI: 10.1080/07853890.2021.1897665
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the prevalence of overweight and obesity in Nigeria in 2020: a systematic review and meta-analysis

Abstract: Background Targeted public health response to obesity in Nigeria is relatively low due to limited epidemiologic understanding. We aimed to estimate nationwide and sub-national prevalence of overweight and obesity in the adult Nigerian population. Methods MEDLINE, EMBASE, Global Health, and Africa Journals Online were systematically searched for relevant epidemiologic studies in Nigeria published on or after 01 January 1990. We assessed quality of studies and conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 52 publications
9
40
0
Order By: Relevance
“…The findings from the multivariate analysis of this study have established that women were more likely to be overweight/obese with increased age (45–49 years), married, urban, with tertiary education, employed, in the highest wealth quintile, Black/African, and resident in the Eastern Cape and KwaZulu-Natal Provinces than underweight women. This finding is consistent with other studies conducted in India ( 44 ) and Nigeria ( 46 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The findings from the multivariate analysis of this study have established that women were more likely to be overweight/obese with increased age (45–49 years), married, urban, with tertiary education, employed, in the highest wealth quintile, Black/African, and resident in the Eastern Cape and KwaZulu-Natal Provinces than underweight women. This finding is consistent with other studies conducted in India ( 44 ) and Nigeria ( 46 ).…”
Section: Discussionsupporting
confidence: 93%
“…In South Africa, about 59% of adults have reported consumption of fruits and vegetables while 49% reported that they consumed fruits only, and about 39% consume an unhealthy diet, and 8% and 5% engage in using tobacco products and risky drinking, respectively ( 14 , 45 ). These findings are similar to evidence from countries, such as Nigeria ( 46 ), Ghana ( 47 ), Namibia ( 48 ), which are countries with an increasing prevalence of overweight/ obesity associated with poor lifestyles. These high prevalence rates of modifiable unhealthy lifestyles can aid in understanding the causes for increased rates of overweight/obesity in South Africa.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results indicated a negative association between the increase of age and EI. Previous studies in Africa have reported a positive association between age and obesity (51,52) . The discrepancy with our study may be associated with the fact that our results are based on the overall age.…”
Section: Discussionmentioning
confidence: 89%